Enhancing the speed and power of 14-17-year-old scuba divers through circular training - Redi E.V.; Konopleva E.N.; Popova E.D. (Theory and Practice of Physical Culture, 2025)
Objective of the study was to assess the extent of development of speed and strength in scuba divers aged 14 to 17, employing the circular training approach. Methods and structure of the study. The research encompassed a cohort of young divers, aged between 14 and 17, who were divided into two groups: a control group and an experimental group, each consisting of 15 participants. Results and conclusions. A contrast of the outcomes of the trials conducted on the experimental and control groups for the exercises under investigation reveals that in terms of speed and power, the experimental group demonstrated a substantial advantage over the control group. Additionally, the athletes in the experimental group achieved superior results at the conclusion of the athletic season in the sprint distances of 50 and 100 meters in flippers, compared to the athletes in the control group. This demonstrates the efficacy of the experimental program in enhancing speed and power abilities.